Rejeitos da indústria de filetagem de tilápia na alimentação de juvenis de tilápia do Nilo (Oreochromis niloticus) - Pacheco, Mateus Laender (2012)
The objective of this study was to evaluate the phy sico-chemical and nutritional characteristics of the waste acid silage of tilapia and performance of juvenile Nile tilapia (Oreochromis niloticus) fed diets consisting of silage. For both experiments were carried out, being the first to evaluate the change in pH and chemical composition of silages made with residues of tilapia with: 5% acetic acid, 3% acetic acid + 2% phosphoric acid and 5% phosphoric acid. The preparation of the silage was the grinding of the residual acidification, homogenising and monitoring pH during 30 days. Analyzes were performed to determine the moisture, crude protein, ether extract and mineral matter of the silages at days 0 , 10, 20 and 30 of storage. The pH at the end of storage time for silage acetic acid, phosphoric acetic and phosphoric + were 4.37, 4.11 and 3.42 respectively. Effect was observed (P<0.05) for the different types of acids used in making silage and for different periods of storage on the parameters analyzed, except for moisture silage acetic acid. The acid silage from tilapia filleting residue acidified with 5% acetic acid showed the chemical composition superior to other treatments may be used in animal feed so to stabilization of pH at 21 days of storage. In the second experiment aimed to determine the coefficients of apparent digestibility of dry matter, crude protein and gross energy of the acid silage of tilapia residues for Nile tilapia (Oreochromis niloticus) in two weight ranges (25 g and 130 g body weight), fed diets with increasing levels of food. 720 juveniles were used, male domination, and 360 with an average weight of 25 g (experiment 1) and 360 with an average weight of 130 g (test 2), packe d in cylindrical tanks with conical bottom capacity of 60 L and 200 L of water , respectively. For the determination of apparent digestibility coefficients, was used a reference diet, which was mixed with the ingredient test (pre-dried) in the proportions 95:05, 90:10, 85:15, 80:20 and 70:30, making the test rations. The apparent digestibility coefficients (%) of dry matter, crude protein and gross energy obtained in trial 1 were respectively 93.57, 97.05 and 94.50 for 5% inclusion, 93.15, 96.74 and 95.08 to 10% inclusion, 92.54, 96.86 and 95.60 to 15% inclusion, 91.92, 95.88 and 94.96 to 20% inclusion, 91.47, 95.39 and 94.80 to 30% of addition, while the values in Test 2 were 84.62, 90.35 and 82.21 to 5% inclusion, 82.85, 90.33 and 83.41 to 10% of inclusion , 83.18, 90.61 and 84.56 to 15% inclusion, 84.12, 86.44 and 85.61 to 2 0% of inclusion and 87.54, 91.20 and 88.65 to 30% inclusion. The waste acid silage of tilapia is food with good protein digestibility. Assays digestibility, it is recommended dietary level of 5% to juvenile 25 g 30% level for juvenile with 130 g. In the third experiment aimed to evaluate the performance and carcass composition of juvenile Nil e tilapia (Oreochromis niloticus) fed diets containing different levels of acid silage of tilapia waste. Five experimental diets were used containing 0% (treatment 1), 5% (treatment 2), 10% (treatment 3), 15% (treatment 4) and 20% (treatment 5) of silage. The performance variables analyzed were: final weight, feed intake, feed conversion, weight gain, survival rate, protein efficiency for gain, specific growth rate and efficiency of nitrogen retention. The carcass composition variables were: deposition of body fat and protein and moisture, protein, ash and fat from the carcass. 1200 juveniles were distributed in completely randomized experimental design in five treatments and eight replicates and 30 fish per experimental unit. Fish were housed in polyethylene tanks with a capacity of 300 L of water. With the exception of survival rate and body fat deposition, the remaining variables had an effect (P<0.05). The acid silage of tilapia filleting residue pre-drought can be included up to 5.83% (21.59% in fresh matter) in diets for juvenile Nile tilapia, for maximum weight gain